(3GdeYdheGJ GdUMajI (B:s (3JfXjegG(B- (3CgejJgG(B- (3aGFOJgG (B/s - (3YRGe, HQLSs ((3OeTb (B:s (3OGQ YdGA GdOjf ,s)
(3jMJhj gPG GdcJGH Ydi OQGSI YdejI ehShYjI Yf GdeYdheGJ GdUMajI h WQb JfXjegG MSH GdWQb GdMOjKI eeG jSgd GSJNOGegG HGbUQ eOI hR GcKQ aGFOI h gPG jbOe GdeDda Ph NHQI GdcHjQI aj Yde GdecJHGJ h GdGQTaI GdWQb GdSgdI h GdeQjMI dJfXje GdeYdheGJ MJi jchf HGecGfgG Gf JbOe NOeGJ LdjdI ddHGMKjf aj TJi GdehGVjY h GdeQLYjGJ s
Keywords: (3GdeYdheGJjIs; (3GdUMGaIs